Analisis Perlakuan Biaya Lingkungan pada Puskesmas Tanggetada: Perspektif Akuntansi Lingkungan - Jumliana, Jumliana; Syahrir, Sasmita Nabila; Nichen, Nichen (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the enviromental cost tretment at the Tanggetada Health Center, Kolaka Regency, within the framework of environmental accounting. The research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with the head of the health center and financial staff, as well as documentation of operational reports. The findings indicate that Tanggetada Health Center has implemented several enviromental cost managment practices, particularly in medical and non-medical waste management. However, these costs have not been classified separately in the financial statementes but are still merged with general operational costs. This reduces the transparency and accountability of financial statement to evaluate the effectiveness of environmental programs. This study emphasizes the importance of separate recording of environmental costs to support transparency, public accountability, and sustaindable development goals. In addition, this study provides practical implications for local goverments as a basis for drafting technical regulations, as well as academic contributions to enrich the literature on environmental accounting in the health sector. Therefore, this study is not only relevant for Tanggetada Health Center but also serves as a reference for other health institutions in integrating environmental accounting to support transparency, accountability and organizational sustainbility.